Enhancing Learning Outcomes in Software Engineering Course through Problem Based Learning and Peer Assisted Learning - Alva, Hannabel Hyacinth; Uma, B.; Shruthi, D. V.; Saroja, C. (Journal of Engineering Education Transformations, 2018)
Learning outcomes are brief statements to describe the significance and fundamental learning achieved by learners, which can be demonstrated at the end of a course. Several researchers of Outcomes Based Education (OBE) suggest that the ability to demonstrate learning is a key element of higher education, which involves a performance of some kind in order to show learning that matters. Knowledge gained must be evident through a demonstration process of some kind depending on the course content. Learning outcomes of Software Engineering course fundamentally require learners to value various engineering issues that contribute to developing an evolving software-intensive system. It is necessary to plan and deliver the required system through efficient software engineering processes, based on knowledge of software development models. In addition, group working skills, inter-group negotiations, planning and time management are also required. This paper outlines the use of Problem-Based Learning (PBL) and Peer Assisted Learning (PAL) techniques that were incorporated in delivering the course on Software Engineering to fourth semester students to enhance the learning outcomes.